Impact of Different Selection Approaches for Identifying Lynch Syndrome-Related Colorectal Cancer Patients: Unity Is Strength - Fanale, Daniele; Corsini, Lidia Rita; Brando, Chiara; Dimino, Alessandra; Filorizzo, Clarissa; Magrin, Luigi; Sciacchitano, Roberta; Fiorino, Alessia; Bazan Russo, Tancredi Didier; Calò, Valentina; Iovanna, Juan Lucio; Francini, Edoardo; et al. (Frontiers in Oncology, 2022)
Lynch syndrome (LS) is an inherited genetic condition associated with increased predisposition to colorectal cancer (CRC) and other tumors and is caused by germline mutations in Mismatch Repair (MMR) or EPCAM genes. The identification of LS carriers is currently based on germline testing of subjects with MMR-deficient (dMMR) tumors or fulfilling clinical criteria, but the most efficient strategies to select patients who should be offered genetic testing are yet not well defined. In order to assess the most suitable selection mode to identify LS-related CRC patients, we retrospectively collected and analyzed all clinical and molecular information of 854 CRC patients, recruited from 2013 to 2021 at the University Hospital Policlinico “P. Giaccone” of Palermo (Italy), 100 of which were selected based on revised Bethesda guidelines, Amsterdam criteria II, or tissue MMR deficiency, and genetically tested for germline variants in LS-susceptibility genes. Our study showed that 32 out of 100 CRC patients harbored germline likely pathogenic/pathogenic variants in MMR genes. The analysis of tissue microsatellite instability (MSI) status according to the revised Bethesda guidelines has been to be the best selection approach. However, using different selection approaches as complementary strategies is useful to identify LS carriers, reducing underdiagnosis of this syndrome.